The Use of Statistics in Policy Research and Decision-making - Dalisay S. Maligalig (Philippine Institute for Development Studies (PIDS), 1994)
Reliable, accurate and timely data and appropriate statistical techniques are key elements to produce quality research and sound decision-making process. This paper investigates the uses of data and statistical methodologies in policy research and planning in the Philippine setting. Based on the number of interviews conducted, it is necessary to identify data gaps and areas for basic and applied research in statistics that may enhance policy research and planning.
Keywords: 330; macroeconometric model; research